Mutifidus in Spinal Stability: Analysis of Inhibition with Muscle Activation Techniques - Blasco E; Bernabe R; Berbel L (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Objectives: To (1) study the relationship between multifidus muscle activation and perception, (2) to explore the correlation between the failure of the multifidus and back pain, when (3) tested with the MAT technique and back pain questionnaire.  Design: Three months prospective before/after quality improvement project. Participants: The participant sample consisted of 34 volunteers (30.5 ± 8.2 years). Intervention: Lumbar disability was calculated using the Oswetry test, along with a neuropropioceptive multifidus response test and perceived exertion (Borg Scale). Results: The results of this study show a high correlation (p =.000) between back pain and the failure of multifidus in the women studied, and also between the failure of the multifidus and perceived exertion in both men and women.  Conclusions: The perception of effort is higher when the muscle fails according to the measure made by the muscle activation techniques.